Involvement of neutrophil hyporesponse and the role of toll-like receptors in human immunodeficiency virus 1 protection (2015)
ABSTARCT: Paracoccidioidomycosis (PCM) is a systemic granulomatous human mycosis caused by fungi of the genus Paracoccidioides, which is geographically restricted to Latin America. Inhalation of spores, the infectious particles of the fungus, is a common route of infection. The PCM treatment of choice is azoles such as itraconazole, but sulfonamides and amphotericin B are used in some cases despite their toxicity to mammalian cells. The current availability of treatments highlights the need to identify and characterize novel targets for antifungal treatment of PCM as well as the need to search for new antifungal compounds obtained from natural sources or by chemical synthesis. To this end, we evaluated the antifungal activity of a camphene thiosemicarbazide derivative (TSC-C) compound on Paracoccidioides yeast. To determine the response of Paracoccidioides spp. to TSC-C, we analyzed the transcriptional profile of the fungus after 8 h of contact with the compound. The results demonstrate that Paracoccidioides lutzii induced the expression of genes related to metabolism; cell cycle and DNA processing; biogenesis of cellular components; cell transduction/signal; cell rescue, defense and virulence; cellular transport, transport facilities and transport routes; energy; protein synthesis; protein fate; transcription; and other proteins without classification. Additionally, we observed intensely inhibited genes related to protein synthesis. Analysis by fluorescence microscopy and flow cytometry revealed that the compound induced the production of reactive oxygen species. Using an isolate with down-regulated SOD1 gene expression (SOD1-aRNA), we sought to determine the function of this gene in the defense of Paracoccidioides yeast cells against the compound. Mutant cells were more susceptible to TSC-C, demonstrating the importance of this gene in response to the compound. The results presented herein suggest that TSC-C is a promising candidate for PCM treatment.